BIODEGRADASI GLUKOSA KONSENTRASI TINGGI DALAM SEQUENCING BATCH REACTOR PADA TAHAP ASIDOGENESA - Mindriany Syafila (Purifikasi, 2003)
In this project, Sequencing batch reactor (SBR) was operated under anaerobic condition during acidogenic phase for high glucose concentration biodegradation. The results show that for COD concentration of 30.000 mg/l the ratio of fill detention time and react time as 2 : 4 (hour/hour) gave the optimum COD removal of 49,2% and for 60.000 mg/l COD the optimum ratio was 2 : 8 (hour/hour) which gave 58,29% COD removal. From the total volatile and production point of view, the optimum condition for both concentrations was 2 : 8 (hour/hour). Biomass concentration was still above 2.000 mg VSS/l, whereas methane was relatively not be able to be detected.